Behavior of multiple lightning dischargers under a tropical thundercloud (2010)
Lightning discharges on ground depend on the electrostatic charges, nature of vegetation, topography and dynamics of the turbulent layer. In designing lightning protectors, one major consideration is the highest point in the surrounding that lightning is directed. The effects of ambient dischargers on lightning protectors were investigated. to determine both the discharge behavior and performance. The starting potential of the discharger configuration increased with clearance of tip of the central discharger from surrounding dischargers, instead of increasing with the average spacing between dischargers. The point of strike of lightning discharge depended on the line of least stress rather than the height clearance from the cloud: which determined the charge structure and dynamics of the cloud particulates